Bone Mineralization and Spinal Fusion Evaluation of a Truss-based Interbody Fusion Device: Ovine Finite Element Analysis with Confirmatory In Vivo Outcomes. Issue 7 (1st April 2022) - Kiapour, Ali; Seim, Howard B.; Atkinson, Brent L.; Lalor, Peggy A.; Block, Jon E.
Abstract : This ovine interbody fusion study compared load-induced strain amplitudes, bone mineralization, and fusion outcomes for different diameter struts in a truss-based spinal implant. Truss devices with smaller diameter struts demonstrated faster fusion consolidation, greater mineralized bone, and less fibrous/chondral tissue than truss devices with larger diameter struts. Abstract : Study Design: Finite element analysis (FEA) and in vivo ovine spinal interbody fusion study. Objective: To determine comparative load-induced strain amplitudes, bone mineralization and fusion outcomes associated with different diameter struts in a truss-based interbody fusion device. Summary of Background Data: Additive manufacturing technology has been employed to develop implants that actively participate in the fusion process. The truss device enables the optimal transfer of compressive and tensile stresses via the struts. Mechanobiologic principles postulate that strut diameter can be regulated to allow different magnitudes of strain distribution within the struts which may affect fusion rates. Methods: Modeling of strain distributions as a function of strut diameter (0.75, 1.0, 1.25, and 1.5 mm) employed FEA that simulated physiologic loading conditions. A confirmatory in vivo ovine lumbar spinal interbody fusion study compared fusion scores and bone histomorphometric variables for cages with 0.75 and 1.5 mm strut diameters. Outcomes were compared at 3-, 6-, and 12-month follow-up intervals. Results: FEA showed an inverse association between strut diameter and peak strain amplitude. Cages with 1.0, 1.25, and 1.5 mm struts had peak strain values that were 36%, 60%, and 73% lower than the 0.75 mm strut strain value. In vivo results showed the mean fusion score for the 0.75 mm diameter strut cage was significantly greater by 3-months versus the 1.5 mm strut cage, and remained significantly higher at each subsequent interval ( P < 0.001 for all comparisons). Fusion rates were 95%, 100%, and 100% (0.75 mm) and 72.7%, 86.4%, and 95.8% (1.5 mm) at 3, 6, and 12 months. Thinner struts had greater mineralized bone tissue and less fibrous/chondral tissue than the thicker struts at each follow-up. Conclusion: Validating FEA estimates, cages with smaller diameter struts exhibited more rapid fusion consolidation and more aggressive osseointegration compared with cages with larger diameters struts. Level of Evidence: 4